2023
DOI: 10.1097/prs.0000000000010575
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in Acellular Dermal Matrix Utilization in Immediate Breast Reconstruction

Abstract: Background: Implant-based reconstruction is the most common method of immediate breast reconstruction in the United States, with acellular dermal matrices (ADMs) playing a significant role in implant support and coverage. This study evaluated recent national trends in ADM use in immediate breast reconstruction and assessed patient characteristics and 30-day complication rates. Methods: The authors queried the American College of Surgeons National Surgical Quality Improvement Program database for all patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This highlights the advantages of using tissue-engineered biocompatible solutions instead of synthetic products. A study by Graziano et al ( 30 ), based on the American Cancer Society database, focused on national outcomes of prepectoral breast reconstruction. They found that most (55%) of direct-to-implant reconstructions utilized ADM.…”
Section: Literature Review Of Tissue- and Bio-engineering Approaches ...mentioning
confidence: 99%
“…This highlights the advantages of using tissue-engineered biocompatible solutions instead of synthetic products. A study by Graziano et al ( 30 ), based on the American Cancer Society database, focused on national outcomes of prepectoral breast reconstruction. They found that most (55%) of direct-to-implant reconstructions utilized ADM.…”
Section: Literature Review Of Tissue- and Bio-engineering Approaches ...mentioning
confidence: 99%